Human Resource Development Perspective in Analyzing the Strategic Environment: Case on Inspectorate Probolinggo Regency - Djony Harijanto; Nik Sarina Nik Md Salleh; Hassan Touati; Ida Bagus Agung Dharmanegara; Hasrudy Tanjung (Mahameru Publisher, 2022)
The purpose of this study was to conduct a strategic environmental analysis at the Inspectorate of Probolinggo Regency, East Java to improve the competence of auditors. The human resource development perspective is used here as a theoretical basis to identify factors both internally and externally, to then be identified and mapped in the form of strengths, weaknesses, opportunities, and threats. The results of this study reveal a description of the competitive environment of the Probolinggo Regency Inspectorate, especially in developing its auditors. Internally, the inspectorate environment is considered to be still less competitive due to the main weakness that stands out, namely the low personal awareness in auditor competency development. But the main strength identified is the internal training methods for auditors that are synchronized both inside and outside the workplace. Externally, the inspectorate environment is considered competitive considering the main opportunities, namely the existence of external training and competency tests for auditors, besides that the organization faces a major threat, namely changes in the landscape and the basis of the audit process in an organization.